eHealth : current evidence, promises, perils and future directions - Hale, Timothy M.; Chou, Wen-ying Sylvia; Cotten, Shelia R.; Khilnani, Aneka (Studies in media and communications, 2018)
This special volume contributes to the rapidly growing body of eHealth research, presenting a selection of multidisciplinary studies on the role and impacts of technology and the Internet in health communication, healthcare delivery, and patient self-management. The use of the Internet and new communication technologies have impacted nearly every aspect of life in recent years. These technologies hold tremendous promise to improve systems of healthcare and enable people to better understand their health and manage their healthcare. However, there are also risks to the use of eHealth technologies. Empirical evidence is urgently needed to examine the use and impacts of eHealth technologies and to inform targeted health communication interventions. Chapters explore both old and new challenges associated with technology-enabled care. These include the persistence of social determinants in shaping Digital Divides in access and use of eHealth technologies, the unintended consequences associated with electronic medical records and pagers on healthcare professionals' ability to control their work time, and how self-tracking and quantification may exacerbate gendered norms of the body and health. Other chapters provide updated information on trends in and predictors of people's trust of health information channels, how people make credibility assessments of online health information, the role of personality traits in perceived benefits in online support group participation, and how online health resources impact people's sense of empowerment and the use of healthcare services. Finally, chapters explore the future potential of eHealth in addressing the needs of underserved communities and guide the creation of new technology-enabled intervention strategies.